Analysis of Nasril Bahar's Actors and Political Strategy as a Member of the House of Representatives of the Republic of Indonesia for the 2004-2029 Period - Latif, Abdul; Amin, Muryanto; Nasution, Indra Kesuma (PERSPEKTIF, 2025)
This study aims to analyze Nasril Bahar as a political actor using his political strategy to maintain power in every legislative election as a House of Representatives of the Republic of Indonesia member for the North Sumatra III Dapil for 2004-2029. This study uses qualitative research methods through Political Actor Theory and Organizational Performance Theory, with data collection techniques through observation, interviews, and documentation. The result of the study is that Nasril Bahar, a member of the House of Representatives of the Republic of Indonesia for five terms, is known as a superior political actor with good communication skills, especially in synergizing to build his constituencies. He used the Muhammadiyah organization to get closer to the residents and their sympathizers through various agendas, such as recitation, haul, and tarjih studies. Nasril upholds the values of Muhammadiyah in its politics, making it a long-term strategy to gain empathy and public vote. This collaboration reflects his dedication to society and the application of religious values in building beneficial and sustainable political relationships.